2017
DOI: 10.1016/j.jamcollsurg.2017.07.866
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of KRAS Mutational Status in Patients with Resectable Colorectal Liver Metastases and Concurrent Extrahepatic Disease

Abstract: with the open approach. This study aims to assess the rate and predictors of conversion and its effect on perioperative outcomes. METHODS: We used the pancreas-targeted NSQIP dataset between 2014 and 2015 to identify patients who underwent MIDP (robotic/laparoscopic) and converted cases. We compared patients' characteristics, perioperative parameters and outcomes in the MIDP and conversion groups. Multivariate analysis (MVA) was used to determine the predictors of conversion and its association with postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In comparison, the present study reported a frequency of 49.5%. Of note, our 2017 study corroborates the authors’ findings, as we found a similarly high rate of KRAS mutations (42.5%) in patients with concurrent EHD 2 . Although the incidence of RAS mutations in such small samples (n = 109 for the study by Lillemoe et al and n = 40 for our study) may be subject to significant random variations, these findings suggest that RAS (or KRAS specifically) mutated tumors may have a propensity to spread outside the liver.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In comparison, the present study reported a frequency of 49.5%. Of note, our 2017 study corroborates the authors’ findings, as we found a similarly high rate of KRAS mutations (42.5%) in patients with concurrent EHD 2 . Although the incidence of RAS mutations in such small samples (n = 109 for the study by Lillemoe et al and n = 40 for our study) may be subject to significant random variations, these findings suggest that RAS (or KRAS specifically) mutated tumors may have a propensity to spread outside the liver.…”
supporting
confidence: 90%
“…Of note, our group presented a study at the 2017 Clinical Congress of the American College of Surgeons that addressed the same question. Our study was entitled “Prognostic relevance of KRAS mutational status in patients with resectable colorectal liver metastases and concurrent extrahepatic disease.” 2 Specifically, in a group of 40 patients who underwent surgery for CRLM and concurrent EHD at Johns Hopkins, we demonstrated that KRAS, which is the most frequently mutated RAS isoform, remained prognostic (TP53 status was not available for analysis). In fact, the risk of death for those with KRAS mutated tumors and EHD was particularly high [hazard ratio (HR): 2.86, 1.04–7.86].…”
mentioning
confidence: 94%
“…Also, the effect of primary tumor site on prognosis differs with the status of RAS mutation. Margonis et al 44 reported that right-sided primary tumor was associated with a worse 5-year OS (43.7% vs. 55.5%) in their KRAS wild-type patients who underwent curative-intent resection for CRLM. However, primary tumor site had no impact on 5-year OS in their KRAS-mutated patients.…”
Section: Molecular Status and Metastasectomy Of Crlmmentioning
confidence: 99%
“…However, primary tumor site had no impact on 5-year OS in their KRAS-mutated patients. 44 In a study of 227 patients undergoing simultaneous curative-intent surgery for synchronous CRLM, right-sided and KRAS-mutated CRLM patients showed the worst OS and DFS, while left-sided and KRAS wild-type CRLM patients had the best OS and DFS. 45…”
Section: Molecular Status and Metastasectomy Of Crlmmentioning
confidence: 99%